Vulnerability assessment in Malaysia government web-based application - Lau, Lee Keng (2020)
The web technology provides various benefits of changing the way of life. People of today, computers seem to be accessible everywhere, whenever want and help make lives easier and more entertaining. It also becomes a tool for government sectors to provide information and services to citizens. Today, to minimize the probability of vulnerabilities exist in web applications, organizations need some methodologies or approaches to increase efforts to protect against web application attack or data breaches. In order to protect organization’s confidential data, there are several methodologies or standards that have commonly used by industry to identify and detect vulnerability exist in web app lications. One of the important steps to ensure the security of web application is conducting vulnerability assessment periodically. This study focuses on studying the OWASP Top 10 most command vulnerability. Manual vulnerability assessment with black box testing was implemented in several Malaysia government web applications to identity their vulnerabilities, the data found was analysed to draw statistical conclusion of the present condition of government web application. Lastly, we also discuss the impact of the vulnerability attacks and proposed possible mitigation strategies.